Tuning in to the radio environment of HD189733b. Issue Volume 15:Issue S354(2019) (June 2019) - Kavanagh, R. D.; Vidotto, A. A.; Fionnagáin, D. Ó; Bourrier, V.; Fares, R.; Jardine, M.; Helling, Ch.; Moutou, C.; Llama, J.; Wheatley, P. J.
Abstract: The hot Jupiter HD189733b is expected to be a source of strong radio emission, due to its close proximity to its magnetically active host star. Here, we model the stellar wind of its host star, based on reconstructed surface stellar magnetic field maps. We use the local stellar wind properties at the planetary orbit obtained from our models to compute the expected radio emission from the planet. Our findings show that the planet emits with a peak flux density within the detection capabilities of LOFAR. However, due to absorption by the stellar wind itself, this emission may be attenuated significantly. We show that the best time to observe the system is when the planet is near primary transit of the host star, as the attenuation from the stellar wind is lowest in this region.